The Diba’iyah Tradition: Strengthening Brotherhood and Love for the Prophet Muhammad (SAW) at Nurul Huda Mosque - Akhmad Choirur Rozikin; Linda Puji Astuti; Ali Akbar Ramadhan; Fina Mu'izzatul Qonita; Irfa Yuhanida Cahyati; Abdullah Nafik; Umi Kholifatus Sangadah; Muhammad Ali Ma'ruf (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study explores the effectiveness of the diba' gatherings in strengthening social bonds and love for the Prophet Muhammad (SAW) in Ngampel Kulon Village. The younger generation faces challenges in maintaining traditions and religious values within the context of a modern social environment. Diba' gatherings are identified as a means to enhance social connections, understand religious teachings, and foster love for the Prophet Muhammad (SAW). This research employs a qualitative method with a descriptive approach to assess the effectiveness of diba'iyah activities. The study aims to evaluate the diba' activities in strengthening social bonds and love for the Prophet Muhammad (SAW) within the community, as well as to identify the positive impacts of these activities. The findings indicate that the diba' activities at Nurul Huda Mosque encourage community participation, strengthen solidarity, and enhance social ties through the regular recitation of prayers every Thursday night. This research contributes practically to education, reinforces religious values, and fosters love for the Prophet Muhammad (SAW). It is hoped that this study will provide guidance for educational institutions and communities in preserving traditions and religious values in the modern era.